2005
DOI: 10.1039/b502444g
|View full text |Cite
|
Sign up to set email alerts
|

Virus–glycopolymer conjugates by copper(i) catalysis of atom transfer radical polymerization and azide–alkyne cycloaddition

Abstract: The Cu(I)-catalyzed ATRP and azide-alkyne cycloaddition reactions together provide a versatile method for the synthesis of end-functionalized glycopolymers and their attachment to a suitably modified viral protein scaffold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
132
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(136 citation statements)
references
References 69 publications
0
132
0
4
Order By: Relevance
“…We employed these particles as reagents in the copper-catalyzed azide-alkyne cycloaddition (CuAAC) reaction, using CuOTf and accelerating ligand 4 under inert atmosphere as has been previously described (61,62). The purified virus was pelleted out of solution, taken into an inert-atmosphere glovebox, and resuspended in degassed 0.1 M Tris buffer (pH 8.0) to prepare for reaction with fluorescein alkyne 3 under our standard conditions, as shown in Figure 5.…”
Section: Conjugation To Genetically Incorporated Azide and Alkyne Groupsmentioning
confidence: 99%
“…We employed these particles as reagents in the copper-catalyzed azide-alkyne cycloaddition (CuAAC) reaction, using CuOTf and accelerating ligand 4 under inert atmosphere as has been previously described (61,62). The purified virus was pelleted out of solution, taken into an inert-atmosphere glovebox, and resuspended in degassed 0.1 M Tris buffer (pH 8.0) to prepare for reaction with fluorescein alkyne 3 under our standard conditions, as shown in Figure 5.…”
Section: Conjugation To Genetically Incorporated Azide and Alkyne Groupsmentioning
confidence: 99%
“…Wang et al first showed that the presence of natural reactive lysine residues on the particle surface and the inherent stability of the particles to temperature, pH, and organic solvents facilitated chemical conjugation (60). This method has been expanded through the use of azide-alkyne chemistry, often called click chemistry (22,59). The ability to create infectious chimeras by insertion of residues and peptides on the capsid surface further allows the multivalent display and controlled chemical modification of the particles (13, 61).…”
mentioning
confidence: 99%
“…3. The amide-bond formations using fluoresceinamine were performed using a modified version of the procedure described by Finn et al [17].…”
Section: Technical Approachmentioning
confidence: 99%